2004
DOI: 10.1097/01.sla.0000114225.46280.fe
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Appraisal of Antireflux Fundoplication

Abstract: Objective: To highlight the current available evidence in antireflux surgery through a systematic review of randomized controlled trials (RCTs). Summary Background Data: Laparoscopic fundoplication is currently suggested as the gold standard for the surgical treatment of gastroesophageal reflux disease, but many controversies are still open concerning the influence of some technical details on its results. Methods: Papers related to RCTs identified via a systematic literature search were evaluated according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
178
3
19

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(217 citation statements)
references
References 106 publications
8
178
3
19
Order By: Relevance
“…However, the Nissen procedure is often followed by troublesome effects. [1][2][3] To reduce the risk of these, partial fundoplications have been developed, and these modifications have been tested in randomized trials. 1;4-6 In the absence of late objective outcomes, some have questioned the durability of partial fundoplications, 7-10 even though longer term clinical outcomes from the trials actually support the application of anterior 180˚ and posterior 270˚ partial fundoplication techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Nissen procedure is often followed by troublesome effects. [1][2][3] To reduce the risk of these, partial fundoplications have been developed, and these modifications have been tested in randomized trials. 1;4-6 In the absence of late objective outcomes, some have questioned the durability of partial fundoplications, 7-10 even though longer term clinical outcomes from the trials actually support the application of anterior 180˚ and posterior 270˚ partial fundoplication techniques.…”
Section: Introductionmentioning
confidence: 99%
“…As the Catarci et al (5) study, the methodological quality of the included studies was very poor, and most of these studies dated from the early of the 90 decade, when the laparoscopy was in the beginning. Other relevant points are the unclear outcome measures and statistical analysis, as detection of publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…The search for better evidence about this subject is growing along this decade. Catarci et al (5) , in a systematic review with meta-analysis, analyzed nine studies comparing total and partial fundoplications: six with open and three with laparoscopic access. They did not find any statistical difference between the groups in the outcomes dysphagia and recurrence of acid reflux.…”
Section: Discussionmentioning
confidence: 99%
“…When the SGV were not divided, the anterior wall of gastric fundus was used for the fundoplication, and not the posterior wall 16,17,18 . A metanalysis published by Catarci et al 19 concluded that the routine division of SGV had no advantage. However, criticism was made to this study, concerning specifi c aspects related to the gastric fundus mobilization such as: instruments, experienced surgical team and the number of different surgeons performing the procedure 20 .…”
Section: Introductionmentioning
confidence: 99%